La proporcionalidad de las sanciones pecuniarias establecidas en la Ley Orgánica de Salud por etiquetado inadecuado de productos. - Villarroel Arciniegas, Jhannela Estefanía (2022)
The present investigation is entitled "THE PROPORTIONALITY OF THE PECUNIARY SANCTIONS ESTABLISHED IN THE ORGANIC LAW OF HEALTH FOR INADEQUATE LABELING OF PRODUCTS". It is originated when there are sanctions to the administered generated by the mislabeling of products, without violating directly the right to health. Hence, the purpose of this research is to describe whether or not there is proportionality of the sanctions for inadequate labeling of products through the proportionality test. For compliance, the research was developed in two parts: first, by treating the constant theoretical framework in 3 units called: the first, the labeling of products, the second, the sanctioning administrative procedure, and, the third, the proportionality of the sanctions. pecuniary the adequate methodological design, to a social legal investigation, is the deductive, synthetic analytical, systematic, bibliographical, logical historical, doctrinal legal, and analytical legal research method; types of bibliographic, field and exploratory research; non-experimental research design. The collection of information has been obtained through the research instruments, as a result of which conclusions and recommendations have been drawn up according to the problem investigated.